TINJAUAN TINGKAT KEPUASAN TAMU TERHADAP KUALITAS PELAYANAN DI RESTORAN COMPASS ROSE DI THE ANMON RESORT BINTAN - Yosua Parhorasan Manullang; Homipa Mania br Perangin-angin (CV. Adiba Aisha Amira, 2025)
The aim of this research is to analyze reviews of guest satisfaction levels regarding service quality at the Compass Rose Rstaurant at The Anmon Resort Bintan. This research uses a descriptive research type with a quantitative approach. The population and the sample in this study was 100 respondents with sampling using a purposive sampling technique. This data collection method by distributing questionnaires to respondents. The research results show that service quality variable has a positive and insignificant effect on guest satisfaction. The results of the t test analysis can be concluded that the calculated t is greater than the significance compared to the t table data, namely 1.765 > 1.658. Thus, the hypothesis in this research there is a positive relationship between the guest satisfaction variable and the service quality variable.